Installation of Hadoop on Windows - Chela, A.K; Sidhu, H.S (International Journal of Computer Sciences and Engineering, 2025)
Technology brings a rapid growth of data. It becomes a challenge to process data with previous methods and applications. The unstructured, scalable, complex data is available through distinct sources like social sites, news, applications and so on. Hadoop is a most demanding development tool for big data because it processes the data in the structured and unstructured form. When you think about Hadoop usually it comes into mind regarding Linux. It is not mandatory for all to learn Linux first and then install Hadoop on a system and then use it. There is an advantage of Linux that it provides basic production and development platform for Hadoop. This paper reflects the light on the variety of platforms, open source systems available for Hadoop installation. Now Hadoop is not only limited to the Linux platform, you can put it on Windows too. Windows is user-friendly and you can install Hadoop without Linux on another hand there are enormous resources by which you can easily go into the Linux environment and place Hadoop. Java is a prerequisite of Hadoop